Diversity of beetles (Arthropoda, Insecta, Coleoptera) associated with coniferous forests in Honduras - Mauricio Hernández; Mauricio Michel; Joel García; Geisy Dueñas; Marcela Moncada; Kevin Amaya; Yensi Yánez; Alejandra Pinto; Gabriela Matamoros; Alejandro Zamora; Gustavo Fontecha (ZooKeys)
Bark beetles are among the primary drivers of tree mortality in coniferous forests worldwide. Individuals belonging to the order Coleoptera were identified across different forest areas in Honduras. Descriptive statistics were used to calculate the number of families, subfamilies, genera, and species collected per department. Moreover, the barcoding approach was used by amplifying and sequencing the mitochondrial COI gene. The intraspecific genetic diversity of Ips apache was also analyzed. 1,131 individuals were examined and 27 genera were identified. Most of the specimens were identified as belonging to the genus Ips, accounting for 53.2% of the total. Xyleborus accounted for 16.5% and Temnoscheila accounted for 10%. Fewer than four individuals were found for fifteen genera. 68% of the specimens were identified to the species level, and all the specimens were identified to the genus level. Ips, Temnoscheila, Xyleborus, Hypothenemus, and Pityophthorus exhibited the most extensive geographic distribution among the sampled sites. At the genus level, Olancho, El Paraíso, and Copán displayed the highest diversity. This study also marks the first report of the genera Xylomeira and Stephanopachys in Honduran pine forests. Within I. apache, evidence of intraspecific genetic diversity was observed, although no population structure was detected. While this research provides an updated inventory of beetle species associated with Honduran coniferous forests, further taxonomic surveys and ecological studies are essential to better understand the spread and impact of bark beetles in pine ecosystems.